Relevansi Kajian Fonetik dan Fonologi dari Al-Aswat al-Lughawiyyah terhadap Pembelajaran Bunyi Bahasa Arab pada Pembelajar Indonesia - Annisa Lutfiyah; Haniah Haniah; Amrah Kasim (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2026)
Arabic has a complex sound system, and many of its phonemes do not have direct equivalents in Indonesian, often causing Indonesian learners to experience difficulty in producing accurate pronunciation. Previous studies consistently indicate phonological problems such as sound substitution, difficulty distinguishing long and short vowels, and challenges in pronouncing emphatic, guttural, and uvular consonants. However, most of these studies remain descriptive and have not been sufficiently linked to a modern Arabic phonetic framework that may support pedagogical improvement. This study aims to analyze the relevance of Ibrāhīm Anīss phonetic and phonological concepts in Al-Aṣwāt al-Lughawiyyah to the teaching of Arabic sounds among Indonesian learners. This research employs a qualitative approach using library research and content analysis of Anīss primary text alongside secondary empirical studies and modern phonetic literature. The findings show that Anīss phonetic framework including articulation mechanisms, sound classification, and acoustic characteristics has significant relevance as a pedagogical foundation for explaining sound production scientifically and systematically rather than relying solely on memorization and imitation. The study recommends integrating Anīss phonetic perspectives into Arabic language instruction in Indonesia to help teachers design more effective pronunciation learning aligned with Indonesian learners phonological characteristics.